1994
DOI: 10.1093/infdis/169.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Epitope-Specific Distribution of IgG Subclasses against Antigenic Domains on Glycoproteins of Human Cytomegalovirus

Abstract: The IgG subclass pattern against linear antibody binding sites on glycoproteins of human cytomegalovirus (HCMV) was investigated in HCMV-positive healthy blood donors, human immunodeficiency virus-infected persons, sera from mothers with primary HCMV infection during pregnancy and their children, and sequential sera from transplant recipients. As antigens, three immunodominant domains capable of inducing neutralizing antibodies during natural infection were selected on glycoproteins gp58/116 (gB) and gp86 (gH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 0 publications
2
17
1
Order By: Relevance
“…The ability of IgG1 immunoglobulins to fix complement and bind to macrophage Fc receptors is thought to be important in the neutralization of free viral particles (57). We conclude that the observed polarization of EBNA1-specific IgG subclasses is most likely a consequence of a predominant Th1 phenotype of responding CD4 + lymphocytes and provides evidence for the polarization of the T-cell response to Th1 in vivo.…”
Section: The Importance Of Cd4 + T Cells In Resistance To Persistent mentioning
confidence: 72%
“…The ability of IgG1 immunoglobulins to fix complement and bind to macrophage Fc receptors is thought to be important in the neutralization of free viral particles (57). We conclude that the observed polarization of EBNA1-specific IgG subclasses is most likely a consequence of a predominant Th1 phenotype of responding CD4 + lymphocytes and provides evidence for the polarization of the T-cell response to Th1 in vivo.…”
Section: The Importance Of Cd4 + T Cells In Resistance To Persistent mentioning
confidence: 72%
“…In addition, we observed a lack of correlation between anti-CMV titers and total IgG or IgG1 concentrations in both, D+/R− and D+/R+ CMV patients one month after HT (before development of CMV disease). It has been reported that reactivity against the antibody binding site on glycoproteins of CMV is detected in the IgG1 subclass [18], which is known to be T-cell dependent [19]. Interestingly enough, decreased baseline IgG1 concentrations were associated with higher risk of CMV disease.…”
Section: Discussionmentioning
confidence: 97%
“…gB-specific IgG 1 is the major subtype induced in response to natural HCMV infection (62). Human IgG 1 is the functional analogue of murine IgG 2a .…”
Section: Vol 78 2004mentioning
confidence: 99%